Effect of typical edible colloid on in vitro digestive characteristics of cheese stick - Pan, Xiaoxue; Ma, Xueying; Tan, Chin-Ping; Liu, Yuanfa; Yang, Wei (Elsevier Ltd, 2025)
Cheese sticks are an oil-in-water emulsified gel system. The addition of natural colloids to the aqueous phase affects the emulsified system and alters its shape and texture. In this study, 12 types of emulsion gel systems for cheese sticks containing different colloid ratios were prepared using carrageenan (CG), locust bean gum (LBG), and guar gum (GG), which are commonly used hydrophilic colloids in commercial cheese sticks. The effects of different colloid on the structure, texture and digestibility of cheese stick were studied under static and dynamic digestion conditions in vitro. The results showed that the addition of colloids inhibited the rate of free fatty acid (FFA) release, with the CG group exhibiting the slowest rate and the lowest NaOH consumption (4.60 mL). Colloids reduced protein digestibility, with the GG group showing a reduction of approximately 12 %. In addition, the CG group had the lowest predicted glycemic index (GI) of 36.36, while GG increased the GI to 41. The results revealed that the colloids impacted the aggregation state and interfacial properties of fats and proteins within the cheese sticks, hindering digestive enzymes from accessing the surface of the particles inside the cluster. This, in turn, inhibited lipid digestibility, thereby altering the digestion and absorption properties of the cheese sticks. Dynamic digestion in vitro was more complete compared to intestinal digestion.